2016
DOI: 10.1136/bmjopen-2016-012970
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the diabetes-tuberculosis treatment outcome (DITTO) study in Pakistan

Abstract: PurposePakistan is faced with an increasing prevalence of diabetes in addition to its existing high burden of tuberculosis (TB). Diabetes has a detrimental effect on treatment outcomes of patients with TB, which may hinder achieving the goals of the End-TB strategy by 2030. We conducted a prospective cohort study to determine difference between treatment outcomes among patients with diabetes and new pulmonary tuberculosis (PTB) and patients without diabetes and new PTB. This would help generate contextual and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…[11][12][13][14] Recent studies in Pakistan have shown more unfavourable outcomes among DS-TB patients with DM; 15,16 however, we could not find any relevant study examining the effect of DM on treatment outcomes among DR-TB patients in Pakistan.…”
contrasting
confidence: 47%
“…[11][12][13][14] Recent studies in Pakistan have shown more unfavourable outcomes among DS-TB patients with DM; 15,16 however, we could not find any relevant study examining the effect of DM on treatment outcomes among DR-TB patients in Pakistan.…”
contrasting
confidence: 47%
“…Nations, belong to the developing part of the world is continuously struggling to combat these chronic conditions due to high prevalence and growing epidemics because of rapid economic, social and life style changes. 12 Studies conducted in Brazil, China and Peru are in line with the results of this research and observed a positive DM-TB association with much higher results. 7,[13][14][15] Anti-tuberculosis medicines worsen the glycemic control and diabetes can cause relapse or worsen the clinical course of TB, that might be a reason of strong positive association, as both conditions are more prevalent in developing countries individually or as comorbid.…”
Section: Discussionsupporting
confidence: 89%
“…The details of study methods have been published previously [ 19 ]. Briefly, the DITTO study was a prospective cohort study undertaken in October 2013 at Gulab Devi Chest Hospital (GDH), a tertiary care hospital in Lahore, Pakistan.…”
Section: Methodsmentioning
confidence: 99%